Sqt1p is an eight‐bladed WD40 protein. Issue 1 (1st January 2016) - Frénois, Frédéric; Legrand, Pierre; Fribourg, Sébastien
Abstract : Ribosome biogenesis in eukaryotes is a complex and highly orchestrated process involving more than 200 accessory factors in addition to ribosomal RNAs and ribosomal proteins. Among the many factors involved, Sqt1p has been reported to specifically bind to uL16 and to act as a chaperone. The crystal structure of full‐length Sqt1p from the yeast Saccharomyces cerevisiae has been solved at 3.35 Å resolution. A SAD experiment at the Se K edge and an S‐SAD experiment on the same selenomethionine‐substituted protein crystal allowed unambiguous positioning of the selenomethionine and Cys residues. On the basis of the atomic structure of Sqt1p, the potential residues involved in uL16 interaction were identified and tested.